Problem set to accompany Bedford-Fowler engineering mechanics : - Fowler, Wallace (Addison Wesley, 1999)
Contents: Statics: vectors, forces, systems of forces and moments, objects in equilibrium, structures in equilibrium,... Dynamics: motion of a point, force, mass, and acceleration, energy methods, momentum methods,...